2023
DOI: 10.1096/fj.202300059rr
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell pyroptosis mediated by METTL3 contributes to the progression of alcoholic steatohepatitis

Abstract: Chronic alcohol consumption is a major risk factor for alcoholic steatohepatitis (ASH). Previous studies have shown that direct injury of hepatocytes is the key factor in its occurrence and development. However, our study shows that the role of Kupffer cells in ASH cannot be ignored. We isolated Kupffer cells from the livers of ASH mice and found that alcohol consumption induced Kupffer cell pyroptosis and increased the release of interleukin-1β (IL-1β). Furthermore, we screened the related m6A enzyme methyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Silencing the m6A enzyme methyltransferase-like 3 (METTL3) alleviates inflammatory factor release by repressing KC pyroptosis in ALD mice. This underscores the pivotal role of KC pyroptosis in ALD mice ( 83 ). Suppression of macrophages contributes to alleviating ALD-associated pathological damage.…”
Section: The Role Of Macrophage Pyroptosis In Liver Diseasesmentioning
confidence: 58%
“…Silencing the m6A enzyme methyltransferase-like 3 (METTL3) alleviates inflammatory factor release by repressing KC pyroptosis in ALD mice. This underscores the pivotal role of KC pyroptosis in ALD mice ( 83 ). Suppression of macrophages contributes to alleviating ALD-associated pathological damage.…”
Section: The Role Of Macrophage Pyroptosis In Liver Diseasesmentioning
confidence: 58%
“…When SIRT1 was knocked down, the protein expression of NLRP3, GSDMD, IL-1β, and IL-18 was significantly increased. 85 In addition, miR-148a levels were significantly reduced in patients with ALD and mouse models. Forkhead box protein O1 (FoxO1), as a transcription factor for miR-148a transcription activation, inhibits the expression of FoxO1 with alcohol and then reduces the expression of miR-148a.…”
Section: Nc-rna Mediated Pyroptosis Pathway In Ald and Nafldmentioning
confidence: 99%
“…Pyroptosis activation in both hepatocytes and liver immune cells exacerbates liver inflammation through intercellular crosstalk. A recent study revealed that alcohol consumption induces pyroptosis in Kupffer cells, which release more IL-1β through active m6A enzyme methyltransferase-like 3 [ 101 ].…”
Section: Cell Death In Liver Diseasementioning
confidence: 99%